Potential candidate genes influencing meat production phenotypic traits in sheep: a review - Ying Han; Muhammad Faheem Akhtar; Wenting Chen; Xiaotong Liu; Mingyue Zhao; Limeng Shi; Muhammad Zahoor Khan; Changfa Wang (Frontiers in Veterinary Science)
This review examines the genetic basis of meat production phenotypic traits in sheep, addressing the challenge of enhancing carcass and meat quality to meet global demand. The article identifies key potential genes associated with vertebral traits, body size, muscle development, and fat deposition across diverse sheep breeds worldwide. Through comprehensive analysis of recent literature (2018–2025), the study synthesizes findings from genome-wide association studies, candidate gene approaches, and transcriptomic analyses. Specific potential genes like VRTN, NR6A1, MSTN, ADIPOQ, LCORL, MEF2B, FASN, FABP4, SCD, DGAT1, BMP and HOX family genes demonstrate significant associations with economically valuable traits. The potential genes influencing meat production phenotypic traits (intramuscular fat contents, growth, vertebral traits and body size traits) have been highlighted in this review. This comprehensive genetic marker catalog serves as a critical resource repository for implementing marker-assisted selection programs, providing breeders and researchers with validated genetic targets to accelerate breeding efficiency and enhance meat production in sheep worldwide.